Digital Activism and Crisis in Nepal: Examining Gen-Z Movements and the Decline of Tourism - Gautam, Deepak; Sapkota, Sushila; Baral, Keshab (Kalika Journal of Multidisciplinary Studies, 2025)
Youth activism has historically shaped social and political change worldwide, and Nepal is no exception. This review and case study analysis synthesizes historical literature (1950–2025), government reports, and real-time data to frame the September (8-10), 2025 “Gen-Z Protests” as a new form of digitally-driven activism and assess their comprehensive multisectoral impact, with particular attention to the tourism sector. The uprising was directly fueled by systemic corruption, nepotism, and elite privilege, with the immediate trigger being the government’s attempted suspension of major social media platforms perceived by youth as intolerable censorship. Underlying structural grievances, including weak governance and high youth unemployment, intensified public frustration. Protesters specifically targeted entrenched elites, commonly referred to as “Nepo Kids.” The movement produced substantial political outcomes, including the withdrawal of the social media ban (September 4) and the resignation of the Prime Minister. Simultaneously, the protests caused severe and immediate economic and human losses: initial government and economist estimate project approximately 21 billion in total damages, 75 deaths, and over 2,316 injuries. The vital tourism sector experienced major disruptions, suffering losses estimated to exceed NPR 25 billion. This case study demonstrates the transformative potential of digitally driven youth activism in Nepal, highlighting its ability to generate tangible political pressure and demand public accountability. It underscores the urgent need for comprehensive governance reforms, enhanced transparency, and measures to address entrenched corruption and elite entitlement. The 2025 Gen-Z movement exemplifies how youth-led digital mobilization can challenge power structures and reshape the political and socio-economic trajectory of a nation. Establishing transparent online feedback systems and youth digital forums within ministries would channel social media activism into constructive dialogue, reducing the risk of uncontrolled digital mobilization and violent collective actions in the future.